2021
DOI: 10.3390/ijms22010400
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of FABP3 in αSyn-Induced Reduction of Septal GABAergic Neurons and Cognitive Decline in Mice

Abstract: In synucleinopathies, while motor symptoms are thought to be attributed to the accumulation of misfolded α-synuclein (αSyn) in nigral dopaminergic neurons, it remains to be elucidated how cognitive decline arises. Here, we investigated the effects of distinct αSyn strains on cognition and the related neuropathology in the medial septum/diagonal band (MS/DB), a key region for cognitive processing. Bilateral injection of αSyn fibrils into the dorsal striatum potently impaired cognition in mice. The cognitive dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Thus, we speculated that HFABP and tau pathology have synergistic effects on AD development. Third, HFABP may also regulate dopamine D2R (dopamine receptor 2) function in the striatum and anterior cingulate cortex and mediates αSyn neurotoxicity in septal GABAergic neurons to affect cognitive function and emotional behavior ( Yamamoto et al, 2018 ; Matsuo et al, 2021 ). Finally, recent studies suggested HFABP was associated with specific features of brain atrophy and white matter Hyperintensities burden, independently of amyloid and tau pathology biomarkers ( Clark et al, 2022 ; Vidal-Piñeiro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculated that HFABP and tau pathology have synergistic effects on AD development. Third, HFABP may also regulate dopamine D2R (dopamine receptor 2) function in the striatum and anterior cingulate cortex and mediates αSyn neurotoxicity in septal GABAergic neurons to affect cognitive function and emotional behavior ( Yamamoto et al, 2018 ; Matsuo et al, 2021 ). Finally, recent studies suggested HFABP was associated with specific features of brain atrophy and white matter Hyperintensities burden, independently of amyloid and tau pathology biomarkers ( Clark et al, 2022 ; Vidal-Piñeiro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%